POTRET STUDI ISLAM DALAM LINTASAN HISTORIS: Dari Masa Klasik, Pertengahan, hingga Modern - Rahman, Abd. Sukkur; Ahmad Muwafiq (STQINIS, 2024)
This article discusses the development of Islamic studies in historical lists. In this case, the historicity of Islamic studies began during the time of the Prophet Muhammad, whose discussions were classified into three periods, namely from the classical period, the medieval period, to the modern period. The presentation of this article is prepared systematically from time to time using a historical approach. The method we use in this research is a qualitative method. In this case, the topic discussion is structured based on descriptive analysis to examine several data related to the research object. The results of this research show that the portrait of Islamic studies in historical history has experienced many developments over time. However, along with the course of history, the study of Islamic studies has also experienced ups and downs caused by several problems, both internal and external. Keywords: Historical Islamic Studies